Nursing students: the use of digital social network to profile nurses - Ketlin Gomes Einhardt; Simoní Saraiva Bordignon; Jamila Geri Tomaschewski-Barlem; Janaina Sena Castanheira; Laurelize Pereira Rocha; Deciane Pintanela de Carvalho (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze the profile of nursing students at a university in southern Brazil and verify the effectiveness of the use of social networks in students' location and adherence. Methods: a quantitative, descriptive and exploratory study, carried out with 314 students through a questionnaire prepared on Google Forms, made available through digital social networks and e-mails. Results: students were women, without training in a technical/assistance nursing course, participants in projects and research groups, with a graduate degree. Furthermore, more than 75% obtained their first job within six months after graduation, more than 80% worked in healthcare, with public employment, workload of up to 40 hours a week, income between four and ten minimum wages, and 92% indicated that they were satisfied and/or very satisfied with the course. Conclusions: the strategic use of social networks enabled greater adherence by the target audience and nursing students' profile design.